Swadharma Wanita Hindu Di Desa Pakraman Mas Kabupaten Gianyar - I Gusti Agung Istri Agung (Jurnal Penelitian Agama Hindu, 2021)
The purpose of this study is to obtain broader information and to provide explanations to various parties regarding the existence of Hindu women in practicing Swadharna in Mas Village, Ubud District, Gianyar Regency. The method used in the study, determining the type and source of data, determining the interview instrument, and studying documents, analyzing data and presenting the results of data analysis. Based on the description and results of the analysis of the existence, constraints and efforts of Hindu women's swadharma in Mas Village, Ubud District, Gianyar Regency, described above, there are several things that can be concluded, namely as follows. The existence of Hindu women in Mas Village can be grouped into three groups. The existence of practicing swadharma can be grouped into three. The existence of practicing swadharma in the family. Existence in carrying out swadharma in the world of work.